KUALITAS TATA KELOLA PERUSAHAAN DALAM MEMODERASI PENGARUH LAPORAN KEBERLANJUTAN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN DALAM INDEKS LQ45) - Nur Intan Mei Hidayati (Jurnal Akuntansi Kompetif, 2026)
The investment paradigm shift towards non-financial aspects has rendered ESG disclosure become crucial for firm valuation. However, high reporting compliance has paradoxically triggered investor skepticism regarding greenwashing risks due to credibility gaps. This study examines the effect of ESG disclosure on firm value, employing Good Corporate Governance (GCG) as a moderating variable. This study employs a quantitative approach with cross-sectional data on companies listed in the LQ45 index of the Indonesia Stock Exchange for the 2024 period. The sample was selected using purposive sampling, resulting in a total of 45 company observations. Data analysis was performed using multiple linear regression and Moderated Regression Analysis (MRA) using Stata software. The results indicate that ESG disclosure has no significant effect on firm value. Similarly, GCG, proxied by the proportion of independent commissioners, does not significantly affect firm value. Furthermore, GCG is proven unable to moderate the relationship between ESG disclosure and firm value. These findings indicate investor skepticism in the Indonesian capital market regarding greenwashing risks, where ESG information is not yet perceived as credible. This suggests that market participants in Indonesia still heavily prioritize financial fundamentals over long-term sustainability incentives. Consequently, companies need to ensure that the implementation of governance and sustainability practices is substantive rather than merely a formality.